PENINGKATAN KETERAMPILAN MELALUI PELATIHAN KERAJINAN TANGAN GANTUNGAN KUNCI BERBAHAN KAIN FLANEL: PEMBERDAYAAN HASIL KREATIVITAS SANTRI P.A & PONPES BINA INSANI YOGYAKARTA - Uju Suji’ah; Sudati Nur Sarfiah; Tri Ratna Herawati; Eko Giyartinzingrum; Eko Prasojo; Leo Dadyo Pamungkas; Ika Destina Puspita (JURNAL PENGABDIAN MANDIRI, 2025)
The purpose of the community service is to provide training in flannel handicrafts to students. The training activity is a follow-up to the previous training, and as a commitment of the community service that P.A & PonPes Bina Insani has been made a foster home, because skills training is not enough to be carried out only once, but will continue to be carried out every 6 months and evaluated the level of ability and interest of the participants. This activity is in collaboration with Rizqun Minallah (RizMina), which is a community empowerment in the field of skills and crafts. The products produced are key chains. There were 27 training participants. The stages carried out in the activity include the preparation, implementation, and evaluation stages, then providing ongoing training assistance in the form of consultation services via WhatsApp, and ready to be scheduled for ongoing activities. The overall training results received a good and satisfactory response, this can be seen from the presence of participants other than students, participants were very enthusiastic about taking the training seriously, making key chains and trying again with their own tastes and creativity. The results of this training activity are expected to inspire participants to become entrepreneurs, and be able to practice on their own without assistance